CODE-SWITCHING AMONG BILINGUAL ENGLISH LEARNERS IN UZBEKISTAN - Shermirzayeva , Makhliyo (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
Bilingualism in Uzbekistan is rapidly expanding, particularly among young English learners. This article explores the phenomenon of code-switching — the alternation of two or more languages in a single speech act — among Uzbek bilingual English learners. The study reveals that learners frequently mix English and Uzbek expressions in daily conversation, reflecting sociocultural identity, language learning motivation, and communicative efficiency. By analyzing linguistic patterns and social attitudes, the paper highlights how code-switching serves both as a learning strategy and as an indicator of bilingual competence.